Copper resistance in the cold: Genome analysis and characterisation of a P IB‐1 ATPase in Bizionia argentinensis - Burgardt, Noelia Ines; Melian, Noelia Agostina; Gonzalez Flecha, Francisco Luis (Environmental Microbiology Reports)
Copper homeostasis is a key process in organisms, with distinctive pathways that have developed according to specific needs but conserve the main resistance mechanisms. These systems are well described in model bacterium, but there is little information about copper resistance in species adapted to cold environments. In this work we explore the repertoire of genes that might be related to copper homeostasis in the genome of Bizionia argentinensis (JUB59-T), a psychrotolerant bacteria isolated from the Antarctic sea water. Several genes were found encoding proteins similar to well-known proteins essential for copper homeostasis, including three sequences of copper-transport P1B-type ATPases. We selected one of these, denoted as BaCopA1, for cloning and expression in Saccharomyces cerevisiae. BaCopA1 was successfully incorporated into yeasts membranes, from where it was removed with detergent. Purified BaCopA1 catalyzes ATP hydrolysis at low temperature. The structural models of different BaCopA1 conformations were obtained and compared to the mesophilic and thermophilic homologous structures. The high conservation of essential residues and the structural similarity between these proteins suggest that they share the same reaction mechanism for copper transport. This is the first report of a psychrotolerant P1B-ATPase expressed and purified in a functional form. Fil: Burgardt, Noelia Ines. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Química y Físico-Química Biológicas "Prof. Alejandro C. Paladini". Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Química y Físico-Química Biológicas; Argentina Fil: Melian, Noelia Agostina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Química y Físico-Química Biológicas "Prof. Alejandro C. Paladini". Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Química y Físico-Química ...